2021
DOI: 10.32479/ijeep.10570
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Capital Structure of the GCC Oil and Gas Companies

Abstract: This study aims to investigate the determinants of capital structure (CS), how they differ among levels (upstream, midstream, and downstream), and to identify Which CS theory is more relevant to the oil and gas companies in the GCC. It uses secondary data of 22 listed oil and gas companies in the GCC over ten years (2010 and 2019). The study will add to the literature as there is few studies about CS in the petroleum industry and it is the only study about the GCC oil and gas sector. Using pooled ordinary leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
5
12
2
1
Order By: Relevance
“…Similar results are reported by Ghani and Bukhari [16], Korkmaz and Karaca [39] and Ahmed and Sabah [40].…”
Section: Financial Factors Determining Capital Structuresupporting
confidence: 91%
“…Similar results are reported by Ghani and Bukhari [16], Korkmaz and Karaca [39] and Ahmed and Sabah [40].…”
Section: Financial Factors Determining Capital Structuresupporting
confidence: 91%
“…The results of this study contradict the research of Marfuah and Nurlaela [17], Sekartaji [1], Sudiyatno et al [4], Tripathi [18], and Watiningsih [2] who found the results of the absence of a positive effect of sales growth on leverage. In addition, it is also inconsistent with research by Fitra and Ashry [12] also Ahmed and Sabah [19] which found that there was no negative effect of sales growth on leverage. Marfuah and Nurlaela [17] also Fitra and Ashry [12] obtained research results where profitability (return on equity) has a positive effect on leverage but on the other hand, Watiningsih [2] actually gets different results, that is profitability has a negative effect on leverage.…”
Section: Prior Researchmentioning
confidence: 69%
“…Marfuah and Nurlaela [17] also Fitra and Ashry [12] obtained research results where profitability (return on equity) has a positive effect on leverage but on the other hand, Watiningsih [2] actually gets different results, that is profitability has a negative effect on leverage. Other researchers, Sudiyatno et al [4] also Ahmed and Sabah [19] found that there was no negative effect of profitability on leverage, while Arifin [20] also Dewi and Sulasmiyati [10] found that profitability had no positive effect on leverage. Research conducted by Arifin [20], Dewi and Sulasmiyati [10], Triyono et al [16], Fitrianingrum et al [21], also Ahmed and Sabah [19] found a positive effect of firm size on leverage.…”
Section: Prior Researchmentioning
confidence: 99%
“…Leverage is an important decision for companies because they have an impact on company value both through the share price channel and the cost of capital (Ahmed and Sabah, 2021). Therefore, in debt policy, companies must be able to create optimal capital structures that maximize share prices or minimize the cost of capital.…”
Section: Literature Reviewmentioning
confidence: 99%